Mr. & Mrs. Smith [videorecording (DVD)] - Liman, Doug; Kinberg, Simon; Pitt, Brad, 1963-; Jolie, Angelina, 1975-; Vaughn, Vince; Powell, John, 1963- (Twentieth Century Fox Home Entertainment, 2005)
A young but bored married couple discover that they are both assassins hired to kill each other.